THE CONSEQUENCES OF TAX COLLECTION ON THE DISCUSSION OF TAX ARRARDS AND INCREASED TAXPAYER COMPLIANCE (Case Study at the Surabaya Gubeng Primary Tax Service Office) - Achmad Daengs GS; Enny Istanti; Diana Zuhro; Bramastyo Kusumonegoro; Ruchan Sanusi; Sutini Sutini (International Journal of Economics and Management Research, 2022)
This study aims to determine the effect of the tax collection and disbursement of arrears of tax on the increase in taxpayer compliance Tax Office Primary Sawahan Surabaya. Model analysis of the data used in this study is to examine the descriptive statistical analysis and provides an overview of how the influence of a letter of reprimand and a letter forced to liquefaction tax arrears and an increase taxpayer compliance in 2010-2012 at the Tax Office Primary Sawahan Surabaya. Based on the results of data analysis using SPSS 16 shows the partial results of hypothesis testing (t-test) or simultaneously (F - test) to prove that the tax collection with a letter of reprimand and a letter has forced, a significant effect on the disbursement of tax arrears with the coefficient of determination shows 46.6%.